Pengembangan Program Penyelarasan strategi Bisnis-TI Badan Pemberdayaan Perempuan dan Keluarga Berencana Provinsi Sumatera Barat - Ruri Juswira (invotek, 2018)
Based on the measurement of Bisnis-IT Strategy Allignment maturity level is found that Badan Pemberdayaan Perempuan dan KB (BPPr & KB) province of west sumatera is still in the first level (initial/adhoc). From the result of the observation that need to be done program planning for supporting role information communication and technology (ICT) in order to support every BPPr & KB activity in reaching its vision and mission. This observation use methodology research and development (RnD) which is used to result product and test the effectivity with many responden 17 persons. Instrument of the observation made to 6 domain area allignmnent strategy business-IT SAMM Luftman with proper modification to the goverment environment. From 6 domain area is found that 36 abstacle factors. This relevant to the obstacle result of Luftman observation. From the thirty sixth obstacle factors found the relational connection to be basic of program planning as observation product. Designing product is proper to current condition and expectation of allignment business-IT strategy that is better After passing to the validation test as matery and content trial and error concept empirically (practicality and effectivity), result of product measurement is considered very practice and effective. There are 42 programs that capable to enhance allignment maturity level Bussiness-IT strategy to the wanted level. Key Words: Allignment Bussiness-IT Strategy, SAMM-Luftman